Studi Etnomatematika: Masjid Sunan Bonang dalam Pembelajaran Geometri - Jazilatul Izah, Shela; Malasari, Putri Nur (Circle: Jurnal Pendidikan Matematika, 2021)
This research was conducted to find mathematical elements in the building of the Sunan Bonang Mosque. This research was conducted at the Sunan Bonang Mosque, Bonang Village, Lasem District, Rembang, Central Java. The method used in this research is qualitative research with an ethnographic approach. The data collection process was carried out by observation, documentation, and interviews. The observation and documentation process was carried out to identify mathematical elements in the building of the Sunan Bonang Mosque. While the interview process was carried out to examine the cultural values of the Sunan Bonang Mosque building. The results showed that there were elements of plane geometry and space geometry in the building of the Sunan Bonang Mosque. The geometric elements identified are square, rectangle, rhombus, circle, triangle, cube, block, tube, prism, and pyramid. So that in learning geometry can use the context of the Sunan Bonang Mosque.The results of this study are expected to provide benefits for contextual learning and be used as an example of the use of mathematical concepts around us.